(untitled) (Letras & Letras, 2016)
Abstract: Since 2013, members of the project ExTrad â€” a program of Continuing professional development carried out at the Federal University of Paraíba (UFPB) â€” have been translating texts in the state of Paraíba (Northeast Brazil). Aimed both at providing translations for the community and at helping on the professional development of the students of the Translation Program of the University, the project has debated a number of ethical issues since its establishment. The paper herein presented discusses some of the ethical issues we have dealt with when translating an 18thÂ century text, on rhetoric, artistic perception and good taste into contemporary Portuguese. Although its theme is apparently non-problematic, colonialist and sexist ideologies underlie the discussions presented on the source text, arising discussions on how to tackle the issue and on how to translate it. This paper does not aim at closing the discussion, nor at presenting definitive solutions, but at opening a debate, by presenting complex translation problems as cases that dwell in a grey area and that require more than easy classifications or translation decisions.